Diagnosis and Management of Hepatobiliary Complications in Autosomal Recessive Polycystic Kidney Disease - Wehrman, Andrew; Kriegermeier, Alyssa; Wen, Jessica (Frontiers in Pediatrics, 2017)
Autosomal recessive polycystic kidney disease (ARPKD) is a congenital hepatorenal fibrocystic disease. The hepatic manifestations of ARPKD can range from asymptomatic to portal hypertension and massively dilated biliary system that results in liver transplantation. Hepatic complications of ARPKD typically present with signs of portal hypertension (splenomegaly and thrombocytopenia) or cholangitis. Liver disease in ARPKD does not always correlate with severity of renal disease. Management of ARPKD related liver disease is largely treating specific symptoms, such as antibiotics for cholangitis or endoscopic treatment for variceal bleeding. If complications cannot be managed medically, liver transplantation may be indicated. This mini-review will discuss the clinical manifestations and management of children with ARPKD liver disease.